The Influence of Puskesmas Head’s Role on Community Satisfaction in Pasaman District - Siska, Marlina; Dasman, Lanin (KARSA Journal of Social and Islamic Culture, 2023)
This study analyzes the effect of the role of the head of the community health center on community satisfaction at UPT Puskesmas Ujung Gading, West Pasaman Regency. Community satisfaction is a function of performance impressions and expectations. If performance is below community expectations, the community feels impressed and dissatisfied. Conversely, if performance meets community expectations, the community will feel happy and satisfied. However, many people still complain about the services provided by the UPT Puskesmas Ujung Gading. This study will analyze the effect of internal roles on community satisfaction at UPT Puskesmas Ujung Gading, West Pasaman Regency, investigate the impact of external positions on community satisfaction at UPT Puskesmas Ujung Gading, West Pasaman Regency, and the effect of internal roles and external roles on community satisfaction at UPT Puskesmas Ujung Gading, West Pasaman Regency. This research will use a quantitative approach with multiple regression analysis techniques to discover these realities. Based on the analysis results, it was found that the internal role has a significant effect on community satisfaction with an Adjusted R Square table value of 0.090, which is 9%, and for a substantial deal of 0.000. External roles considerably affect community satisfaction with an Adjusted R Square table value of 0.058, 5.8%, and for a significant deal of 0.000. Internal and external functions have a positive and significant effect on community satisfaction with an Adjusted R Square table value of 0.150,